If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + -6 = 9 Reorder the terms: -6 + Z = 9 Solving -6 + Z = 9 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + Z = 9 + 6 Combine like terms: -6 + 6 = 0 0 + Z = 9 + 6 Z = 9 + 6 Combine like terms: 9 + 6 = 15 Z = 15 Simplifying Z = 15
| d=15(-16) | | 4x^2=-16x | | (4/5)x^2-x+(11/10)=0 | | -315+x=-155 | | -18+y=-40 | | 12x+73=15x+61 | | 2x2/5+5x/6=10 | | 2x+3=5x+4-3x | | a*.1=44.54 | | 3x-4=5-x+2/3 | | 2(x-4)-3(x+2)=8(x+5) | | 10+z=12 | | 7x-5/6=4x+2/3 | | 11+r=20 | | y+24=25 | | 3x+2=4x+3-x | | x=-15(-3) | | 81x^8-18x^4+1=0 | | 6e+40=e | | 6(15-x)-3x=196-42x+9x | | 30=p+22 | | k+26=30 | | 6*0-10y=30 | | 29=14+z | | 9jk-kj+5jk= | | 400(50)=20.000 | | 400x=20.000 | | 2x-5=5x-16 | | -2(v-4)=6v-16 | | 10x+6*0=30 | | 5(2x+3)-17=-3(x+8) | | 2t^2+15t+20=0 |